ICF-BASED PLANNING OF PHYSICAL THERAPY INTERVENTIONS FOR PATIENTS WITH MULTIPLE SCLEROSIS - Павлова, Тетяна; Мерзлий, Микола (SWorldJournal, 2026)
The article substantiates an ICF-based algorithm for planning physical therapy interventions for patients with multiple sclerosis and describes the content of a four-week rehabilitation program consisting of two weeks of outpatient rehabilitation followed